Systematic Literature Review Penerapan Metodologi Agile Dalam Berbagai Bidang - mutia sari zulvi (Politeknik Caltex Riau, 2021)
The development of the telephone or cell phone and the internet, its existence has an influence on various aspects of life. Both individual life, social and related to the world of business or business. In addition to simplifying and accelerating the process of communication and information, information technology is also used in business or business activities. Many communication and information tools are used in the activities of the business world, one of which is the application. Applications are generally divided into 3 platforms, namely desktop, web, and mobile. In building an application, it takes a software development methodology that is used for the smooth design or development of an application. Web-based application development has many methods that can be used, one of which is the Agile method. This method is one of the well-known methods because it is considered actual and easy to use. This study uses a systematic literature review method that displays an analysis of agile methods in various fields covering a total of X papers published from 2017 to 2021. This study aims to answer several research questions, namely: 1) Knowing what trend models are used in agile methods, 2) Knowing what fields implement agile methods in their application development, 3) Knowing the application platforms that are most often used in agile methods. The purpose of this research is as a literature study related to the use of Agile and it is hoped that readers will gain knowledge about what Agile methods will be used for their applications. Keywords: Platform, Agile, Systematic Literature Review.